Double Victimization on Refugee Children in Pekanbaru - Rio Tutrianto; Syahrul Akmal Latif; Syakira Rahmadita (International Conference On Law And Social Sciences, 2024)
Foreign refugees in Indonesia are often perceived as unwelcome arrivals. Their presence is frequently rejected by the local community. This rejection further exacerbates the already existing chain of victimization experienced by them. In victim studies, children are categorized as vulnerable individuals susceptible to becoming victims. The status of being a refugee increases the level of victimization experienced by them. Although the number of refugees cannot be considered significant, their presence in Indonesia remains puzzling. This is due to the lack of strong and comprehensive regulatory frameworks to serve as guidelines for managing, regulating, and protecting the presence of refugees in Indonesia. Indonesia has also not ratified the 1951 Convention Relating to the Status of Refugees and its 1967 Protocol. Through a qualitative approach, this research explains that becoming a refugee or an overseas refugee is extremely challenging for everyone, especially for those classified as vulnerable groups. Refugee children do not have the opportunity to study in reputable and quality educational institutions. The chaos and vulnerability inherited from the refugee situation can disrupt the physical, intellectual, psychological, cultural, and social development of children. Meanwhile, in refugee camps or community houses, access to healthcare, decent housing, and nutritious food always remains uncertain.